Carboxypeptidase E-∆N Promotes Proliferation and Invasion of Pancreatic Cancer Cells via Upregulation of CXCR2 Gene Expression - Sangeetha Hareendran (International Journal of Molecular Sciences, 2019)
Pancreatic cancer is one of the leading causes of cancer-related mortality worldwide. The molecular basis for the pathogenesis of this disease remains elusive. In this study, we have investigated the role of wild-type Carboxypeptidase E (CPE-WT) and a 40 kDa N-terminal truncated isoform, CPE-ΔN in promoting proliferation and invasion of Panc-1 cells, a pancreatic cancer cell line. Both CPE-WT and CPE-ΔN were expressed in Panc-1 and BXPC-3 pancreatic cancer cells. Immunocytochemical studies revealed that in CPE transfected Panc-1 cells, CPE-ΔN was found primarily in the nucleus, whereas CPE-WT was present exclusively in the cytoplasm as puncta, characteristic of secretory vesicles. Endogenous CPE-WT was secreted into the media. Overexpression of CPE-ΔN in Panc-1 cells resulted in enhancement of proliferation and invasion of these cells, as determined by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) cell proliferation assay and Matrigel invasion assay, respectively. In contrast, the expression of CPE-WT protein at comparable levels to CPE-ΔN in Panc-1 cells resulted in promotion of proliferation but not invasion. Importantly, there was an upregulation of the expression of CXCR2 mRNA and protein in Panc-1 cells overexpressing CPE-ΔN, and these cells exhibited significant increase in proliferation in a CXCR2-dependent manner. Thus, CPE-ΔN may play an important role in promoting pancreatic cancer growth and malignancy through upregulating the expression of the metastasis-related gene, CXCR2.